Instagram: A Place to Share, Learn, and Grow - Vania Putri Kartika; Vivink Erlianfika (CV Grasta Glory, 2026)
Today, Instagram is one of the most popular social media platforms among individuals in this digital era. However, although Instagram can be seen as an entertainment source for some people, it is also used as a source for sharing, gaining knowledge, and personal development. As such, this essay shall highlight how Instagram can be used as a platform for sharing and growing together. Instagram provides many functions ranging from posting, stories, and reels whereby people can express themselves and share information with other people (Instagram, 2023). Moreover, Instagram also gives its users access to a number of resources related to education. Thus, individuals get to learn in different areas of knowledge such as languages, studies, and personal development (UNESCO, 2022). Additionally, Instagram contributes to personal development by stimulating creativity, increasing self-confidence, and offering opportunities to build a personal brand and grow a business (Harvard Business Review, 2021). In spite of all its advantages, there are certain problems like misuse, spread of false information, and social comparison which pose problems that need to be taken into account (Pew Research Center, 2024). Hence, one should use this social media network wisely. In general, Instagram can be an extremely useful means of communication.